2003
DOI: 10.1103/physrevlett.91.095501
|View full text |Cite
|
Sign up to set email alerts
|

Creeping Friction Dynamics and Molecular Dissipation Mechanisms in Glassy Polymers

Abstract: The dissipation mechanism of nanoscale kinetic friction between an atomic force microscopy tip and a surface of amorphous glassy polystyrene has been studied as a function of two parameters: the scanning velocity and the temperature. Superposition of the friction results using the method of reduced variables revealed the dissipative behavior as an activated relaxation process with a potential barrier height of 7.0 kcal/mol, corresponding to the hindered rotation of phenyl groups around the C-C bond with the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
128
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 24 publications
14
128
0
Order By: Relevance
“…5 The results are in agreement with experiments studying the velocity dependence, 4 the temperature dependence, 10 and the jump force distribution. 11 However, the experimental situation is not well represented, since a one-spring model cannot reproduce both the resonance frequency of the cantilever, and the experimentally found lateral stiffness which is dominated by the contact.…”
Section: Simulation Of the Stick-slip Processsupporting
confidence: 80%
“…5 The results are in agreement with experiments studying the velocity dependence, 4 the temperature dependence, 10 and the jump force distribution. 11 However, the experimental situation is not well represented, since a one-spring model cannot reproduce both the resonance frequency of the cantilever, and the experimentally found lateral stiffness which is dominated by the contact.…”
Section: Simulation Of the Stick-slip Processsupporting
confidence: 80%
“…Equation 7 is based on a sinusoidal surface potential continuously overcome during the course of frictional sliding, which Sills and Overney experimentally determined as 7 kcal/mol on glassy polystyrene. 37 This activated process corresponds directly with the hindered rotation of the phenyl ring side chains about their bond with the backbone, supporting the contribution of intrinsic molecular relaxation to elastomeric friction. In a similar SFM friction study on poly(methyl methacrylate), Hammerschmidt et al.…”
Section: Stochastic Adhesive Modelmentioning
confidence: 99%
“…creep models that consider barrier-hopping fluctuations of periodic surface potentials with slips occurring at lower energy values than prescribed by the potential barriers. [34][35][36] Sills and Overney 37 showed that hindered, or frozen, relaxation states of an amorphous polymer could be activated in the course of a frictional sliding process, and thus, give rise to a barrier-hopping fluctuation not unlike the one observed for highly ordered surfaces. Friction-rate isotherms obtained with a SFM tip on glassy polystyrene could be collapsed to a master curve according to a ramped creep model 34,35 , Figure 3, which considers a single asperity sliding over a corrugated surface potential that is biased due to the motion of the driven tip, i.e.…”
Section: Stochastic Adhesive Modelmentioning
confidence: 99%
“…There are many theoretical and experimental evidences showing the important role played by temperature in the friction phenomena. [11][12][13][20][21][22][23] The main temperature effect is the reduction in the friction force in the stick-slip region of the friction versus driving velocity curves. This reduction has been observed at high temperatures and is explained by the existence of thermally activated jumps of the tip.…”
Section: Surface Disorder With Temperaturementioning
confidence: 99%